2005
DOI: 10.1021/ma050896y
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-like Array Formation in Phase Separation Induced by Radical Polymerization

Abstract: A unique domain structure was found in liquid−liquid phase separation induced by radical polymerization of 4-chlorostyrene monomer in the presence of random copolymer poly(dimethylsiloxane-co-diphenylsiloxane). Over a wide range of temperature and initial monomer composition, poly(4-chlorostyrene)-rich droplets with narrow size distribution were generated by phase separation, and these droplets hardly coalesced by collisions. With the growth of droplet size, droplets gradually filled the space and spontaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…It was also found that, as quench is in process, the evolution of the wetting layer thickness could cross over to a faster growth when the preferential component was the minority component. At the initial time, the polymer mixture exhibited the usual droplet morphology based on the formation mechanism of nucleation and growth in the off-critical phase separation [206,207]. With the increasing time, the coalescence of the droplets occurs.…”
Section: -6mentioning
confidence: 99%
“…It was also found that, as quench is in process, the evolution of the wetting layer thickness could cross over to a faster growth when the preferential component was the minority component. At the initial time, the polymer mixture exhibited the usual droplet morphology based on the formation mechanism of nucleation and growth in the off-critical phase separation [206,207]. With the increasing time, the coalescence of the droplets occurs.…”
Section: -6mentioning
confidence: 99%
“…Reaction‐induced phase separation during isothermal polymerization has been studied to control the morphology of aromatic polymers 10–17. The isothermal polymerization can induce phase separation from homogeneous liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…Isothermal polymerizations can induce phase separation from homogeneous solution26–31 and the reaction‐induced phase separation during isothermal solution polymerization is a very useful method for the morphology control of poor processable polymers, because the morphology is created by the phase‐separation of oligomers 32, 33. This method is not limited by the processability of polymers.…”
Section: Introductionmentioning
confidence: 99%